Analisis Kriminalisasi Terhadap Santet Sebagai Tindak Pidana - Lingga Adi Dharma; Ifahda Pratama Hapsari; Hardian Iskandar (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
Santet is generally difficult to understand or understand its meaning, as a supernatural belief phenomenon involving the use of magic or black magic, has become part of local culture in Indonesia. Santet, from some opinions, can also cause someone to become a victim due to the misuse of witchcraft which is used as a medium to cause harm, illness, or even death, including criminal acts. This article focuses on an analysis of the criminalization of witchcraft as a criminal act. Through an exploration of the existing legal basis, this research seeks to provide a deeper understanding of how criminal law can be applied in order to suppress an act of witchcraft practice that harms the community. This research provides a clear picture of the role of criminal law in dealing with the phenomenon of witchcraft, although challenges related to belief, culture, and the unclear definition of the practice remain complex. Thus, this article is intended to provide a basis for further discussion regarding the criminal analysis of witchcraft as a criminal offense, with the aim of creating fair law enforcement and protecting the public from the negative impact of supernatural practices.